Diagnosis and Treatment of Acanthamoeba Keratitis (Ukrainian Journal of Ophthalmology, 2026)
Objective: Review the clinical characteristics, diagnosis, treatment and visual results in patients diagnosed with Acanthamoeba keratitis (AK). Demonstrate the importance of early diagnosis and of prompt and effective treatment.Material and methods: Retrospective study of 14 eyes in the same number of patients diagnosed with AK, treated at Centro Visi?n between July 2008 and June 2012. All the cases were confirmed by smear and/or culture. Two groups were established: early and late diagnosis. Treatment was carried out with propamidine and polyhexamethylene biguanide. After the infection had been eliminated, final visual acuity and duration of treatment were recorded. Results: The most frequently affected group was aged between 21 and 40 years (9 cases). Only two eyes (14.3%) were correctly diagnosed initially as AK. Eleven patients (78.6%) were contact lens wearers. The most common sign was diffuse infiltrate (62.3%); perineural infiltrate was only seen in one case. Five patients were diagnosed within the first thirty days (early diagnosis group) and nine cases were diagnosed later (late diagnosis group). Median visual acuity in the early diagnosis group was 20/40, and in the late diagnosis group it was 20/400. The median duration of treatment in the early diagnosis group was six months, and in the late diagnosis group it was ten months. Conclusions: The majority of the eyes (85.7%) were initially erroneously classified as keratitis resulting from other causes. When AK is diagnosed early there is a better visual prognosis, and also prolonged treatment will not be necessary.
Keywords: акантамебний кератит; контактні лінзи; полігексаметілен бігуанід; пропамідін